Pengaruh Kegiatan Penyuluhan Pertanian Lapangan (PPL) dan Produksi Padi Terhadap Pendapatan Petani di Kecamatan Sungai Raya Kabupaten Kubu Raya - B01111027, Dian Yuli Aryanti (Jurnal Pembangunan dan Pemerataan, 2016)
Human resources have an important role in agricultural activities ranging from managerial to keaspek keterampilan.Untuk aspects that need agricultural extension field or resource development program. This study aims to determine the effect of the field of agricultural extension activities and productivity of rice plants against the income of farmers in the district Sungai Raya.                This study uses primary data taken directly from respondents through the questionnaire with a population of 30 respondents. The model is a model of descriptive data analysis using SPSS (Statistical Product and Service) version 21.               The independent variable in this study is; agricultural extension activities field (X1), the production of rice (X2) and farmers' income as dependent variable (Y). Before testing the hypothesis testing instruments that include validity, reliability, classic assumption test, test normalitas, multolineritas test, test hetoskedesitas, then the hypothesis test with simultaneous test (F test) partial test (t test).               Based on the results of the research, that the field of agricultural extension activities and significant positive effect on the income of farmers in the district SungaiRaya, production of rice and significant positive effect on the income of farmers in the district of West Kalimantan SungaiRaya.Key word: Activity of Extension Agricultural,  Production of rice ,and  Farmer’s Income